Two ZnII‐based MOFs constructed with biphenyl‐2, 2′, 5, 5′‐tetracarboxylic acid and flexible N‐donor ligands: syntheses, structures and properties. Issue 6 (13th May 2020) - Su, Feng; Yu, Jinyang; Zhou, Chengyong; Li, Shaodong; Ma, Pengyi; Zhang, Xuhui; Wang, Zhijun
Abstract : Two Zn II ‐based coordination polymers were prepared by solvothermal synthesis using biphenyl‐2, 2′, 5, 5′‐tetracarboxylic acid and ZnCl2 ·4H2 O under the control of flexible N‐donor ligands. In the structures, the Zn II ions adopt distorted tetrahedral geometries and are bound by tetracarboxylate ligands to produce a two‐dimensional layer in one complex and a three‐dimensional network in the other. Furthermore, the luminescence properties of the complexes were investigated and the ferroelectric properties of one of the complexes were shown to be a result of its polar point group C 2 v . Abstract : Two new Zn 2+ ‐based metal–organic frameworks (MOFs) based on biphenyl‐2, 2′, 5, 5′‐tetracarboxylic acid, i.e. H4 ( o, m ‐bpta), and N‐donor ligands, namely, poly[[(μ4 ‐biphenyl‐2, 2′, 5, 5′‐tetracarboxylato)bis{[1, 3‐phenylenebis(methylene)]bis(1 H ‐imidazole)}dizinc(II)] dimethylformamide monosolvate dihydrate], {[Zn2 (C16 H6 O8 )(C14 H14 N4 )2 ]·C3 H7 NO·2H2 O} n or {[Zn2 ( o, m ‐bpta)(1, 3‐bimb)2 ]·C3 H7 NO·2H2 O} n (1 ) {1, 3‐bimb = [1, 3‐phenylenebis(methylene)]bis(1 H ‐imidazole)}, and poly[[(μ4 ‐biphenyl‐2, 2′, 5, 5′‐tetracarboxylato)bis{[1, 4‐phenylenebis(methylene)]bis(1 H ‐imidazole)}dizinc(II)] monohydrate], {[Zn2 (C16 H6 O8 )(C14 H14 N4 )2 ]·H2 O} n or {[Zn2 ( o, m ‐bpta)(1, 4‐bimb)2 ]·H2 O} n (2 ) {1, 4‐bimb = [1, 4‐phenylenebis(methylene)]bis(1 H ‐imidazole)}, have been synthesized under solvothermal conditions. The complexes were characterized by IR spectroscopy, elemental analysis, single‐crystal X‐ray diffraction and powder X‐ray diffraction analysis. Structurally, the ( o, m ‐bpta) 4− ligands are fully deprotonated and combine with Zn 2+ ions in μ4 ‐coordination modes. Complex 1 is a (3, 4)‐connected porous network with honeycomb‐like [Zn2 ( o, m ‐bpta)] n sheets formed by 4‐connected ( o, m ‐bpta) 4− ligands. Complex 2 exhibits a (2, 4)‐connected network formed by 4‐connected ( o, m ‐bpta) 4− ligands linking Zn 2+ ions in left‐handed helical chains. The cis ‐configured 1, 3‐bimb and 1, 4‐bimb ligands bridge Zn 2+ ions to form multi‐membered [Zn2 (bimb)2 ] loops. Optically, the complexes show strong fluorescence and display larger red shifts compared to free H4 ( o, m ‐bpta). Complex 2 shows ferroelectric properties due to crystallizing in the C 2 v polar point group.